Analisis Spasial Pendapatan dan Pengeluaran Rumah Tangga untuk Perencanaan Smart Economy Berbasis Wilayah di Kota Gorontalo - Irwan Wunarlan (Transbahasa, 2026)
This study aims to analyze household income characteristics and expenditure patterns as a basis for smart economy planning in the implementation of a smart city in Gorontalo City. A quantitative descriptive approach with an administrative spatial analysis was employed using questionnaire data from 150 households across nine districts: Kota Timur, Kota Utara, Kota Selatan, Kota Barat, Kota Tengah, Dumbo Raya, Dungingi, Sipatana, and Hulonthalangi. The analyzed variables included monthly household income and expenditures on food and beverages, transportation, electricity, water, gas, telephone and internet credit, and hygiene. The findings reveal that 72% of respondents earned less than IDR 3,000,000 per month, indicating limited household economic capacity. Food and beverages accounted for the largest average monthly expenditure (IDR 813,333; 48.61%), followed by transportation (IDR 301,667; 18.03%) and electricity (IDR 196,167; 11.72%). Spatial analysis showed that East City, South City, Central City, North City, and Hulonthalangi districts had a higher concentration of low-income households, whereas Sipatana and Dungingi exhibited relatively stronger household economic conditions. These findings suggest that smart city planning in Gorontalo City should extend beyond technological development by emphasizing economic empowerment, affordability of digital services, mobility efficiency, and equitable access across districts. Therefore, smart economy planning should be grounded in an understanding of household economic conditions to ensure that smart city policies are inclusive and responsive to the needs of the community, particularly low-income households.